Association of occupational strain with selected factors and hair cortisol as potential biomarker among lecturers in community colleges, Peninsular Malaysia - Ismail, Nada (2015)
Introduction: Occupational stress occurs when job requirement do not match the capabilities, resources and needs of the workers, and occupational strain is one of the important source of occupational stress that poses a threat to the health of workers and also to the health of organizations. Lecturer is one of the position that mostly reported having high strain and nowadays, the stressfulness of teaching has been recognized as a big number of academic workers are reporting stress, depression and anxiety caused by their work. Hair cortisol was used to measure the occupational strain because it may represent a long term exposure to the stress related hormone Objectives: To determine the prevalence of occupational strain, the organizational factors that contributed to occupational strain as well as the association between hair cortisol level and occupational strain among lecturers in Community Colleges. Methodology: A cross sectional study was conducted and 189 workers participated in this study. The validated self-administered Malay version of Job Content Questionnaire (JCQ) was used to verify the socio-demographic background, factors contributed to work strain which is organizational factors and the stress level of the respondents. Cronbach’s alpha coefficients revealed for organizational factors were 0.75 for decision latitude,0.84 for social support and 0,80 for psychological job demand and job insecurity. The hair cortisol level was analysed using ALPCO Cortisol ELISA Kit. Result: The response rate was 87.1%. The prevalence of occupational strain among the respondents was 25.9% and this was based on the respondent’s psychological job demand and decision latitude. Hierarchical multiple regression showed that job insecurity (95% CI: 1.08-2.09) and social support (95% CI: 0.69-0.91) also have significant associations with occupational strain. However, there were no significant association between occupational strain and hair cortisol level (P=0.063). The sensitivity of hair cortisol analysis was only 25.53% while the specificity was 91.47%. Conclusion: The study showed there is a significant association between occupational strain and social support as well as job insecurity. The low sensitivity of hair cortisol analysis showed that hair cortisol cannot be proposed as biological marker of occupational strain.